Active droplet sorting in microfluidics: a review. Issue 5 (15th February 2017) - Xi, Heng-Dong; Zheng, Hao; Guo, Wei; Gañán-Calvo, Alfonso M.; Ai, Ye; Tsao, Chia-Wen; Zhou, Jun; Li, Weihua; Huang, Yanyi; Nguyen, Nam-Trung; Tan, Say Hwa
Abstract : This review presents the fundamentals of different active methods for sorting droplets in microfluidics. Abstract : The ability to manipulate and sort droplets is a fundamental issue in droplet-based microfluidics. Various lab-on-a-chip applications can only be realized if droplets are systematically categorized and sorted. These micron-sized droplets act as ideal reactors which compartmentalize different biological and chemical reagents. Array processing of these droplets hinges on the competence of the sorting and integration into the fluidic system. Recent technological advances only allow droplets to be actively sorted at the rate of kilohertz or less. In this review, we present state-of-the-art technologies which are implemented to efficiently sort droplets. We classify the concepts according to the type of energy implemented into the system. We also discuss various key issues and provide insights into various systems.